Peran Orang Tua dalam Memenuhi Hak Pendidikan Anak Perempuan di Desa Tanjungsari : Studi Implementasi Pasal 31 Ayat (1) UUD 1945 - Robiatul Fitriah; Yogi Nugraha; Nadya Putri Saylendra (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to determine the role of parents in fulfilling the right to education for girls based on the implementation of Article 31 Paragraph (1) of the 1945 Constitution in the region. This study uses a qualitative descriptive approach with data collection methods in the form of interviews, observations, and documentation. Informants in this study consisted of village heads, parents, and girls who dropped out of school. Data analysis was carried out using the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results of the study revealed that some parents showed a high awareness of the importance of education for girls and provided real support by sending their children to school to a certain level of education. However, there are also parents who still limit their children's education to only a certain level, mainly due to limited economic reasons and the influence of cultural values ​​rooted in society. Factors such as economic dependence on girls and the view that higher education is not necessary for women are obstacles in realizing equal access to education. The implementation of Article 31 Paragraph (1) of the 1945 Constitution at the village level has not been optimal because there are no specific policies or programs from the village government that actually guarantee the right to education for girls. This study concludes that parental involvement plays an important role in addressing the inequality of access to education for girls in rural areas, and further support is needed from the government and the community to create an environment that is more supportive of girls' education. The implementation of more inclusive policies based on the needs of the local community is also very necessary to ensure that girls' right to education can be properly fulfilled.